Systematic Literature Review (SLR): The Role Of Environmental Management Accounting In Enhancing Green Competitive Advantage And Sustainable Performance In The Hospitality Industry In Indonesia - Belandina Anita Sere Sihombing; Desak Nyoman Lia Lestari; Rela Sari (International Journal of Economics, Business and Innovation Research, 2024)
The hospitality industry in Indonesia faces significant challenges in balancing business growth with environmental responsibility. This study aims to review the role of Environmental Management Accounting (EMA) in enhancing green competitive advantage and sustainable performance in the hospitality sector. Using a Systematic Literature Review (SLR) approach, this study analyzes 10 articles from a total of 60 relevant articles identified through Google Scholar and Semantic Scholar from 2019–2024. The selected articles cover research related to EMA and the factors influencing its implementation. The findings reveal that EMA plays a crucial role as a mediator in the relationship between green competitive advantage and sustainable performance. Studies by Saputra et al. (2023) and Noor & Bano (2023) indicate that implementing EMA can strengthen competitiveness and improve environmental management efficiency, contributing to sustainable performance outcomes. Additionally, institutional and regulatory pressures, as discussed by Che Ku Kassim et al. (2020) and Elhossade et al. (2020), encourage hospitality companies to adopt EMA practices effectively. EMA serves a strategic role in supporting sustainability in Indonesia's hospitality sector by helping firms enhance green competitiveness and environmental efficiency. Committed management and strong regulatory frameworks are essential for successful EMA implementation. This study recommends stronger management commitment and regulatory support to promote broader EMA adoption in the hospitality industry for long-term sustainability.